Two Step Selection for Bias in β Chain V-J Pairing - Levi, Reut; Louzoun, Yoram (Frontiers in Immunology, 2022)
The beta chain rearrangement in T cells is a two-step process where first D beta and J beta bind, and only then V beta is joined to the complex. We here show that the frequency of human and mouse V beta - J beta combinations deviates from the one expected based on each gene usage frequency. This bias is observed mainly in functional (F) rearrangements, but also slightly in non-functional (NF) rearrangements. Preferred V beta - J beta combinations in F clones are shared between donors and samples, suggesting a common structural mechanism for these biases in addition to any host-specific antigen-induced peripheral selection. The sharing holds even in clones with J beta 1 that share the same D beta 1 gene. V beta - J beta usage is correlated with the Molecular Weight and Isoelectric Point in F clones. The pairing is also observed in the Double Positive cells in mice thymocytes, suggesting that the selection leading to such a pairing occurs before thymic selection. These results suggest an additional structural checkpoint in the beta chain development prior to thymic selection during the T cell receptor expression. Understanding this structural selection is important for the distinction between normal and aberrant T cell development, and crucial for the design of engineered TCRs.